2017
DOI: 10.3233/jad-170447
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway

Abstract: Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 78 publications
2
51
0
Order By: Relevance
“…Previous studies have indicated that BDNF expression in the salivary glands changes in response to stress [28,29]. Moreover, it is well established that the concentration of BDNF in blood decreases following stress in humans and various animal species [14,22]. The present findings indicate that social isolation stress also induces a reduction of BDNF in saliva and blood.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have indicated that BDNF expression in the salivary glands changes in response to stress [28,29]. Moreover, it is well established that the concentration of BDNF in blood decreases following stress in humans and various animal species [14,22]. The present findings indicate that social isolation stress also induces a reduction of BDNF in saliva and blood.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, tyrosine kinase B (TrkB), which is the BDNF receptor, is also reduced in the hippocampus in schizophrenia [21]. Additionally, model rats with mild chronic stress show a reduction in the concentration of serum BDNF [14], and stressful life events can reduce the serum concentration of BDNF in humans [22]. It is well established that saliva is an extremely useful diagnostic source for several diseases in humans, and could eventually replace blood sampling [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Since brain BDNF crosses the blood-brain barrier (Pan, Banks, Fasold, Bluth, & Kastin, 1998), is seems reasonable to assume that blood BDNF protein levels resemble those in the brain. This assumption is reinforced by several evidences: serum BDNF is positively associated to cortical levels of Nacetyl aspartate, a marker of neuronal integrity (Lang, Hellweg, Seifert, Schubert, & Gallinat, 2007); brain pathologies are associated to a decrease in BDNF levels in brain and blood, whereas successful therapeutic interventions can increase BDNF levels in these two compartments (Autry & Monteggia, 2012;Diniz & Teixeira, 2011;Gezen-Ak et al, 2013); the severity of neurological symptoms, such as the degree of cognitive impairment, is correlated to serum BDNF levels (Corrêa et al, 2016;K€ uster et al, 2017;Zhang et al, 2012). Based on these evidences, we assume that central and peripheral levels of BDNF are associated.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the ethics committees of both study centers, University of Konstanz and Ulm University, Germany. The study was part of a controlled clinical trial investigating the effect of physical exercise and cognitive training on cognition as well as on biological and electrophysiological parameters (cf., Fissler et al, ; Küster et al, , ; Laptinskaya et al, ). All participants provided written informed consent prior to study participation.…”
Section: Methodsmentioning
confidence: 99%